Book Review: Alastair Gunn and Ruth Walker. (2003) Buddhism and Environmental Ethics in Context. Kuala Lumpur: Centre for Civilisational Dialogue, University of Malaya. - Bucher, S. (2008)
Alastair Gunn and Ruth Walker. (2003) Buddhism and Environmental Ethics in Context. Kuala Lumpur: Centre for Civilisational Dialogue, University of Malaya.